Projeto preliminar de um elevador automotivo portátil para veículos de até 3500 kg - Moreira, Maria Luísa Mendes (Universidade Federal Rural do Semi-Árido, 2018)
Automotive lifts are equipment that facilitates the assembly and maintenance of vehicles. Commonly for its complete elevation makes if necessary specific equipment that are usually found in mechanical workshops due to its complexity and robustness. It makes interesting the study of a more simplified and easier to handle equipment. During the evolution of this research it will be possible to size a portable automotive lift capable of completely raising the vehicle in a simple and safe way. For the development of this research will be carried out a case study, market and use of CAD tools to simulate and help predict the behavior of the equipment. The present project seeks to unite knowledge in manufacturing processes with the needs found in the market and thus to analyze the viability of the design and better ways of building the mechanism. According to the response obtained from the implementation of the methodology adopted, it is expected that at the end of this project a correct dimensioning in order to guarantee simplicity, effectiveness and safety.
Keywords: Elevador automotivo; CAD; Simulação; Projeto; Automotive lift; CAD; Simulation; Project; ENGENHARIAS::ENGENHARIA MECANICA